Impact of flipped classroom method in physical education on the intrinsic motivation, self-efficacy, and learning satisfaction: A meta-analysis - Qingxu Wu; Zhenxiao Han; Zikang Hao; Jiping Chen; Yang Pan (PLoS ONE, 2025)
Background Flipped classroom (FC) is a novel teaching method. To assess its effectiveness in teaching physical education in schools, a systematic review and meta-analysis were conducted with the aim of exploring the Impact of FC method in PE on the intrinsic motivation, self-efficacy, and learning satisfaction. Methods As of February 2025, a comprehensive search was conducted in the Web of Science (WoS) and China National Knowledge Infrastructure (CNKI) databases to identify studies pertaining to FC style PE instruction and its impact on students’ intrinsic motivation, self-efficacy, and learning satisfaction. Results Total 13 studies were included in this study. The results demonstrated that, compared to traditional teaching methods, the FC model significantly improved intrinsic motivation, self-efficacy, and learning satisfaction. These findings underscore the notable positive impact of the FC approach on multiple educational outcomes. Subgroup analyses revealed that the FC model significantly enhanced students’ intrinsic motivation across different countries, various PE subjects, differing class sizes, and diverse student populations. In terms of learning satisfaction, the FC approach demonstrated positive effects in subgroups involving Chinese participants, PE subjects focused on dance, and varying class sizes. Conclusion Integrating the FC model into school PE classes has been shown to enhance students’ intrinsic motivation, self-efficacy, and learning satisfaction. However, further high-quality research is essential to solidify and extend these findings.